Synthesis of alginate-curcumin nanocomposite and its protective role in transgenic Drosophila model of Parkinson's disease. - Siddique, Y.H.; Khan, W.; Singh, B.R.; Naqvi, A.H. (ISRN pharmacology, 2013)
The genetic models in Drosophila provide a platform to understand the mechanism associated with degenerative diseases. The model for Parkinson's disease (PD) based on normal human alpha-synuclein ( ? S) expression was used in the present study. The aggregation of ? S in brain leads to the formation of Lewy bodies and selective loss of dopaminergic neurons due to oxidative stress. Polyphenols generally have the reduced oral bioavailability, increased metabolic turnover, and lower permeability through the blood brain barrier. In the present study, the effect of synthesized alginate-curcumin nanocomposite was studied on the climbing ability of the PD model flies, lipid peroxidation, and apoptosis in the brain of PD model flies. The alginate-curcumin nanocomposite at final doses of 10(-5), 10(-3), and 10(-1)?g/mL was supplemented with diet, and the flies were allowed to feed for 24 days. A significant dose-dependent delay in the loss of climbing ability and reduction in the oxidative stress and apoptosis in the brain of PD model flies were observed. The results suggest that alginate-curcumin nanocomposite is potent in delaying the climbing disability of PD model flies and also reduced the oxidative stress as well as apoptosis in the brain of PD model flies.